FINANCIAL PERFORMANCE ASSESSED FROM QUICK RATIO, CURRENT RATIO, RETURN ON INVESTMENT, NET PROFIT MARGIN IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2017 - 2019 - Titis Prasetyaningrum; Eny Kustiyah; Fithri Setya Marwanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 in terms of the Quick Ratio, Current Ratio, Return On Investment, and Net Profit Margin. This type of research is quantitative research. The population in this study were all 182 manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. The sampling technique used was purposive sampling and the number of samples in this study were 11 companies. The data collection technique is secondary data, so the data is taken from the financial statements of Manufacturing Companies listed on the IDX 2017-2019 through the Indonesia Stock Exchange website (www.idx.co.id). Testing the research hypothesis using multiple linear regression analysis through SPSS 26. The results of this study indicate that each company, judging from the ratios owned, has increased and decreased quite varied. From the points obtained, it can be seen that the companies that have the best level of financial health during 2017 to 2019 are PT HM Sampoerna Tbk, PT Tempo Scan Pasific Tbk and PT Mayora Indah Tbk. And the company that has the most unhealthy level of financial health during 2017 to 2019 is PT Wismilak Inti Makmur Tbk. Keywords: Financial Performance, Quick ratio, Current ratio, Return on investment, Net profit margin